The Behavioral Toxicity of Insect Growth Disruptors on Apis mellifera Queen Care - Litsey, Eliza M.; Chung, Siwon; Fine, Julia D. (Frontiers in Ecology and Evolution, 2021)
As social insects, honey bees (Apis mellifera) rely on the coordinated performance of various behaviors to ensure that the needs of the colony are met. One of the most critical of these behaviors is the feeding and care of egg laying honey bee queens by non-fecund female worker attendants. These behaviors are crucial to honey bee reproduction and are known to be elicited by the queen’s pheromone blend. The degree to which workers respond to this blend can vary depending on their physiological status, but little is known regarding the impacts of developmental exposure to agrochemicals on this behavior. This work investigated how exposing workers during larval development to chronic sublethal doses of insect growth disruptors affected their development time, weight, longevity, and queen pheromone responsiveness as adult worker honey bees. Exposure to the juvenile hormone analogue pyriproxyfen consistently shortened the duration of pupation, and pyriproxyfen and diflubenzuron inconsistently reduced the survivorship of adult bees. Finally, pyriproxyfen and methoxyfenozide treated bees were found to be less responsive to queen pheromone relative to other treatment groups. Here, we describe these results and discuss their possible physiological underpinnings as well as their potential impacts on honey bee reproduction and colony performance.